The Pareto chart of caries intensity evaluation for children with allergic diseases - Кривенко, С. А.; Безрук, В. М.; Kryvenko, L. (IEEE, 2015)
An Information and Communication Technology for caries intensity evaluation for children with allergic diseases is proposed. The method is based on a Pareto chart and a digital convergence prism. The Pareto chart is one of the seven basic tools of quality control. The method has been tested during the clinical examination of 110 children of individuals by using a probe, mirror and cotton rolls, and simply counts the number of decayed, missing (due to caries only) and restored teeth.
Keywords: Distributed databases; Statistical analysis; Telecommunications; Information and communication technology; Information systems; Servers